2002
DOI: 10.1002/jnr.10442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enriched environments with different durations and starting times on learning capacity during aging in rats assessed by a refined procedure of the Hebb‐Williams maze task

Abstract: Cognitive function as measured by the Hebb-Williams maze task was examined in Fischer 344 male rats that had been exposed to an enriched environment for periods of variable duration and at different starting ages. In one experiment, rats were exposed to environmental enrichment from weaning until the age of 2.5, 15, or 25 months. The results of 12 problems of the Hebb-Williams maze task showed that the enriched rearing condition improved the learning ability in all the age groups; however, factor analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 36 publications
(44 reference statements)
4
83
2
1
Order By: Relevance
“…For instance, it decreases freezing responses to a fear-conditioned context (Barbelivien et al 2006;Benaroya-Milshtein et al 2004) and reduces anxiety-like behavior (e.g., Galani et al 2007), an observation recently confirmed in aged rats (Leal-Galicia et al 2008). The impact of environmental enrichment on aging-related impairments might depend on the exposure duration, longer enrichment leading to attenuation or even complete prevention of the age-related cognitive decline (Bennett et al 2006;Kobayashi et al 2002) but also on the age of enrichment onset Freret et al 2011). We recently found that environmental enrichment during the whole post-weaning life limited the age-related alterations of Morris water maze learning capabilities in rats; it also ameliorated memory persistence for at least 24 h after the end of training (Harati et al 2011).…”
Section: Introductionmentioning
confidence: 93%
“…For instance, it decreases freezing responses to a fear-conditioned context (Barbelivien et al 2006;Benaroya-Milshtein et al 2004) and reduces anxiety-like behavior (e.g., Galani et al 2007), an observation recently confirmed in aged rats (Leal-Galicia et al 2008). The impact of environmental enrichment on aging-related impairments might depend on the exposure duration, longer enrichment leading to attenuation or even complete prevention of the age-related cognitive decline (Bennett et al 2006;Kobayashi et al 2002) but also on the age of enrichment onset Freret et al 2011). We recently found that environmental enrichment during the whole post-weaning life limited the age-related alterations of Morris water maze learning capabilities in rats; it also ameliorated memory persistence for at least 24 h after the end of training (Harati et al 2011).…”
Section: Introductionmentioning
confidence: 93%
“…For example, food availability could be made variable in both space and time [101]. Enrichment protocols and early stress paradigms could be applied [102,103].…”
Section: Is Innovation Selected Upon Directly or Is Itmentioning
confidence: 99%
“…In addition to modifying hippocampal morphology, complex housing also enhances performance on a number of hippocampal-dependent learning tasks. The most welldocumented augmentation of learning after complex housing is in spatial tasks such as the Morris water maze and Hebb-Williams maze (Pham et al 1999;Kobayashi et al 2002). However, there is also evidence that environmental enrichment enhances Pavlovian fear conditioning in mice (Rampon et al 2000;Duffy et al 2001;Tang et al 2001).…”
mentioning
confidence: 99%